(untitled) (Conferencea, 2023)
In this article, the formation of surfaces in the "Drawing geometry" lessons and their presentation in the drawing is an important factor in shaping the students’ creative spatial imagination. formation of skills to improve their activity, what methods and technologies today’s youth should have.